Effect of lavender (Lavender angustifolia) extract on food consumption, melatonin, leptin and reproductive parameters in male Syrian hamsters (Mesocricetus auratus) - Emine İnci Balkan; Bülent Gündüz (European Journal of Biological Research)
Lavender (Lavandula angustifolia) is a plant of medicinal and economic importance. This study investigated the effects of lavender extract at different doses on metabolism and reproductive physiology in male Syrian hamsters (Mesocricetus auratus) under long photoperiod (16L; 16 hours of light, 8 hours of darkness). Male Syrian hamsters aged 6-8 weeks were administered different doses of lavender extract dissolved in saline intraperitoneally every day at the same time (12:00-13:00 h) for 21 days. A significant decrease in food consumption was observed in the group treated with 200 mg/kg of lavender extract (p<0.05). The effects of the 100 mg/kg and 200 mg/kg doses on body weight were also noted. Blood samples for hormone measurement were collected at two different times of the day (12:00 h and 00:00 h) at the end of the experiment. It was shown that melatonin levels significantly increased at the 100 mg/kg dose of lavender extract in both times (p<0.05). However, no significant difference was found between the light and dark phases at the 200 mg/kg dose (p>0.05). A significant decrease in testosterone levels was observed compared to the control group. Similarly, no significant difference was detected between the light and dark phases at the 200 mg/kg dose (p>0.05). No significant differences were observed in testis histology between the control and treatment groups. In conclusion, lavender extract has positive effects on metabolism, but it may have negative effects on the reproductive system at high doses.